Realizing the Benefits of Massification - Fazal Rizvi (DUZ Academic Publishers, 2022)
This article suggests that the rapid growth in gross enrollment ratios within many systems of higher education has mostly failed to deliver the expected benefits of massification, due largely to inadequate planning with respect to issues of purpose, capacity, and quality.